2001
DOI: 10.1144/jgs.158.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Late Devensian glaciotectonic deformation at St Bees, Cumbria: a critical wedge model

Abstract: Glaciotectonic deformation of the Late Devensian sediments exposed at St Bees, Cumbria is represented by minor extensional faults resulting from ice-sheet loading of the unconsolidated sediments accompanied by thrusting and folding. The highly deformed northern part of the section has numerous thrust faults associated with fold structures that verge predominantly to the SE, but with some NW-vergent (backthrust) structures. A high-resolution seismic reflection survey confirms that the thrust structures form a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Glasser et al, 2011;Carrivick et al, 2012;Hannesdóttir et al, 2015), or else using geophysically-obtained stratigraphy data to produce restored cross-sections via consideration of plain strain conditions (e.g. Williams et al, 2001). …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Glasser et al, 2011;Carrivick et al, 2012;Hannesdóttir et al, 2015), or else using geophysically-obtained stratigraphy data to produce restored cross-sections via consideration of plain strain conditions (e.g. Williams et al, 2001). …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Work on the sedimentary and structural legacy of ice streams (Clark and Stokes, 2003), although limited, is also increasing. For example, work by Evans and Ó Cofaigh (2003) in southern Ireland, Harris et al, (1997) and Thomas and Chiverrell (2007) in northwest Wales, Williams et al, (2001) in Cumbria, and Thomas et al, (2004) and Roberts et al, (2007) on the Isle of Man, has shown that the sediments at the margin of the Late Devensian Irish Sea Ice Stream were pervasively deformed as it retreated from its maximum extent in the Celtic Sea (Scourse and Furze, 2001). The polyphase deformation histories recorded by these often complex sedimentary successions have been equated with repeated phases of readvance during retreat of a highly dynamic ice sheet margin (Thomas and Chiverrell, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Interpretations of the primary sedimentary and tectonic structures within the exposure were made using line drawings (e.g. Williams et al, 2001;Phillips et al, 2002). Particle size analyses on the key lithofacies were conducted on riffled bulk samples of c. 200 g using wet sieving.…”
Section: Geological and Structural Investigationmentioning
confidence: 99%